Parkinson’s disease model in zebrafish using intraperitoneal MPTP injection - Omar, Noor Azzizah; Kumar, Jaya; Teoh, Seong Lin (Frontiers in Neuroscience, 2023)
Introduction Parkinson’s disease (PD) is the second most common neurodegenerative disease that severely affects the quality of life of patients and their family members. Exposure to 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) has been shown to reflect behavioral, molecular, and proteomic features of PD. This study aimed to assess the protocol for inducing PD following MPTP injection in adult zebrafish. Methods Fish were injected with 100 μg/g of MPTP intraperitoneally once or twice and then assessed on days 1 to 30 post-injection. Results Between one-time and two-time injections, there was no significant difference in most locomotor parameters, expressions of tyrosine hydroxylase-2 (th2) and dopamine transporter (dat) genes, and dopaminergic neurons (tyrosine hydroxylase positive, TH+ cells) counts. However, caspase-3 levels significantly differed between one- and two-time injections on the day 1 assessment. Discussion Over a 30-day period, the parameters showed significant differences in swimming speed, total distance traveled, tyrosine hydroxylase-1 (th1) and dat gene expressions, caspase-3 and glutathione protein levels, and TH+ cell counts. Days 3 and 5 showed the most changes compared to the control. In conclusion, a one-time injection of MPTP with delayed assessment on days 3 to 5 is a good PD model for animal studies.